Spatial analysis of the distribution pattern of vertical residential complexes in the city of Baghdad - Haseeb, Huda Jasim; Al-Taie, Ayad Ashour Hamza (Al-Adab Journal, 2021)
This research clarified the types of spatial analysis and their application to government and investment vertical residential complexes and their distribution to 14 municipalities, in the city of Baghdad. Short time and one of the most prominent results of the research is that the types of spatial analysis (closest neighbor contour, average center, standard distance, actual average center and direction of distribution, density analysis) in the study area. It was observed through the study that government and investment vertical residential complexes took the random distribution pattern, i.e. the divergent pattern in the study area, and that the concentration of residential complexes was on the Karkh side more than the Rusafa side, as a result of the acceptance and desire of the population to live in the vertical residential complexes more than on the Rusafa side.